169 Red Sky in Morning: A Case of Concurrent Hematospermia and Anorgasmia. Issue 1 (1st April 2022) - Yee, A.; Tennenbaum, D.; Rabinowitz, D.; Khurgin, J.
ABSTRACT: Introduction: Hematospermia, or blood in the ejaculate, usually follows a benign course. However, it can be a source of considerable anxiety in patients. Similarly anorgasmia, or the inability to achieve orgasm despite adequate sexual stimulation may cause significant psychological distress. These rare conditions pose unique challenges for diagnosis and treatment and have distinct considerations when they occur together. Objective: We present a case of concurrent hematospermia and anorgasmia with the diagnostic and treatment procedures for both. We report that simultaneous cystoscopy, electroejaculation (EEJ), transurethral resection of ejaculatory ducts (TURED), and seminal vesiculography is safe and effective as a diagnostic and treatment modality. Methods: Medical history, physical exam, laboratory analyses of blood, urine, and semen were performed. A cystoscopic video of the prostatic urethra was recorded while performing EEJ, in order to observe hematospermia under direct vision. A TURED was then performed to evaluate the ejaculatory ducts and to facilitate seminal vesiculography. Results: A healthy 36 year old man reported avoidance of all sexual activity after a few episodes of hematospermia due to extreme fear. He continued to note bloody discharge on occasion in the morning, attributing this to bloody nocturnal emissions. Despite normal erectile function, he adamantly avoided all sexual activity including masturbation. Prior STI workup, cystoscopy, urinalysis, urine and semen cultures were all negative. Prior treatments with finasteride, NSAIDs, and antibiotics failed to reduce the frequency of hematospermia, and he had minimal improvement in libido with cabergoline and buproprion. Concurrent urethroscopy and EEJ revealed initial hematospermia from bilateral ejaculatory ducts with normal, white emission after several seconds. A TURED and direct seminal vesiculography revealed hypoplastic seminal vesicles bilaterally. The patient tolerated the procedure well and had resolution of hematospermia post-operatively. He reports improvement in libido and willingness to attempt sexual activity. Conclusions: Despite a usually benign clinical course, hematospermia can provoke great anxiety in patients to the point of avoidance of sexual activity. We propose a causal relationship between hematospermia and our patient's sexual dysfunction and anorgasmia, as the patient reports renewed interest in sex after his hematospermia resolved post-operatively. A thorough evaluation to rule out more serious pathology and to address the patient's anxiety included simultaneous cystoscopy, EEJ, TURED, and seminal vesiculography. This was both safe and effective in diagnosis and treatment of concurrent hematospermia and anorgasmia, and is the first video demonstration of simultaneous cystoscopy and EEJ reported in the literature to our knowledge. Disclosure: No